The effects of organizational conflicts on team effectiveness in a Malaysian statutory body institutions - Mohd, Idaya Husna; Omar, Muhammad Khalil; Tengku Asri, Tengku Nural (2016)
Working in teams is usually expected to improve organizational effectiveness; however, there are several challenges that would affect team effectiveness.While team members are usually empowered to find a solution to a problem, this raises the question of effectiveness of the team itself, especially in terms of conflict that usually occurs when working in teams. Conflict was suggested to be positive and useful for organizations, but also provides negative effects, interferes with team performance, and reduces satisfaction because it triggers stress and causes team members to perform ineffectively.Therefore, this study investigated the effect of conflicts on team effectiveness in a Malaysian statutory body. Three types of organizational conflicts, namely task, relationship, and process conflicts, were studied, as well as which of the three has the most implication on team effectiveness. A survey was conducted among employees in the Malaysian statutory body regarding organizational conflict and team effectiveness. The results highlighted the understanding of organizational conflict and team effectiveness from the employees’ perspective, which showed both task and process conflicts having moderate positive relationships with team effectiveness, while no relationship was observed between relationship conflict and team effectiveness.This study offers recommendations that can help the organization to improve.